Innovative financing models for low carbon transitions: Exploring the case for revolving funds for domestic energy efficiency programmes. (November 2015) - Gouldson, Andy; Kerr, Niall; Millward-Hopkins, Joel; Freeman, Mark C.; Topi, Corrado; Sullivan, Rory
Abstract: The IEA has estimated that over the next four decades US31 trillion will be required to promote energy efficiency in buildings. However, the opportunities to make such investments are often constrained, particularly in contexts of austerity. We consider the potential of revolving funds as an innovative financing mechanism that could reduce investment requirements and enhance investment impacts by recovering and reinvesting some of the savings generated by early investments. Such funds have been created in various contexts, but there has never been a formal academic evaluation of their potential to contribute to low carbon transitions. To address this, we propose a generic revolving fund model and apply it using data on the costs and benefits of domestic sector retrofit in the UK. We find that a revolving fund could reduce the costs of domestic sector retrofit in the UK by 26%, or £9 billion, whilst also making such a scheme cost-neutral, albeit with significant up-front investments that would only pay for themselves over an extended period of time. We conclude that revolving funds could enable countries with limited resources to invest more heavily and more effectively in low carbon development, even in contexts of austerity. Highlights: Examines the need for substantially higher levels of low carbon investment. Explores the need for innovative financing mechanisms such as revolving funds. Shows that revolving a fund could reduce the cost of UK retrofit by £9 billion or 26%. Also shows that a revolving fund could make retrofit cost-neutral in the long term. Concludes that revolving funds could dramatically increase low carbon investment.